Changes in frequency of spontaneous oscillations in procerebrum correlate to behavioural choice in terrestrial snails - Samarova, Elena; Balaban, Pavel (Frontiers in Cellular Neuroscience, 2009)
The aim of our study was to understand functional significance of spontaneous oscillations of local field potential in the olfactory brain lobe of terrestrial snail, the procerebrum (PC). We compared changes in frequency of oscillations in semi-intact preparations from snails trained to percept the same conditioned odor as positive (associated with food reinforcement) or negative (associated with noxious reinforcement). In vivo recordings in freely behaving naïve snails showed a significant decrease of spontaneous PC oscillations frequency during a stage of tentacle withdrawal to odor presentation. In in vitro preparations from naïve snails, a similar decrease in frequency of the PC oscillations to odor presentation was observed. Changes in frequency of the oscillations to cineole presentations in the “aversive” group of snails (demonstrating withdrawal) were much more pronounced than in naïve snails. No significant difference in responses to 5 and 20% cineole was noted. Changes in the spontaneous oscillations frequency in the snails trained to respond with positive reaction (approach) to cineole depended on the concentration of the applied odor, and these responses were qualitatively similar to responses of other groups during the first 10 s of responses to odor, but significantly different (increase in PC oscillations frequency) from the responses of the aversively trained and naïve snails in the interval 11-30 s, which corresponds to the end of the tentacle withdrawal and timing of decision making (approach or escape) in the free behaving snails. Obtained results suggest that frequency of the PC lobe spontaneous oscillations correlate to the choice of behavior in snails: withdrawal (decrease in frequency) or approach (increase in frequency) to the source of odor.